Aspectos hidrobiogeoquímicos e ambientais do sistema estuarino de Raposa, MA - FREITAS, Christiano Teixeira de (2024)
The study aims to evaluate the dynamics of hydrobiochemical variables in estuarine water, observing the seasonal influence and the contribution of human activities. The research focuses on parameters such as salinity, pH, transparency, nitrite, nitrate, dissolved oxygen, and nutrients. Data collection was conducted during different seasonal periods (rainy and dry) and in various areas of the estuary (Eólica, Mangue, and Baía). The analysis involved techniques for measuring the physical and chemical parameters of the water, as well as the use of statistical models to interpret the results. Salinity, pH, transparency, nitrite, and nitrate showed a negative relationship with the rainy period due to the greater influx of freshwater. Dissolved oxygen and nutrients showed a positive correlation with precipitation, suggesting that increased rainfall favors primary productivity. During the rainy season, there was an increase in water temperature, dissolved oxygen, and nutrients, indicating an intensification of biochemical dynamics and primary productivity. The study concludes that seasonality significantly affects water quality and nutrient availability in the estuary. It highlights the importance of continuous monitoring and integrated studies for the development of predictive models that support decision-making and the implementation of sustainable management practices. This work provides valuable insights for the conservation of biodiversity and the ecosystem integrity of the Raposa estuary. The research is essential for understanding the impacts of human activities on estuarine ecosystems and for developing mitigation and sustainable management strategies for these crucial environments.